Respon pakar media dan ulama terkait vaksin covid-19 - Atina Mumtaza; Ahmad Ali Fikri (Universitas Nusantara PGRI Kediri, 2022)
Reviewing the rapid spread of covid 19 and the resulting risks will have a big impact if not handled immediately. Regarding this, the government is implementing a vaccination program especially for the Indonesian people at the end of 2020. This program has brought various responses from various groups, including medical experts and scholars, because it has caused a lot of polemics. The purpose of this study was to determine the response of medical experts and scholars regarding the covid 19 vaccine. This research approach is quantitative, a type of survey research with data collection through a Likert scale to support the accuracy of the research. The population is medical experts and scholars in the Gajah sub-district, Demak district. The research sample amounted to 10 respondents with cluster random sampling in data collection. The results of this study are medical experts and scholars fully support the program, even giving a positive response, with an index of 85% (strongly agree). With this research, it is hoped that the public will be aware of the importance of the Covid-19 vaccination and be able to increase motivation in participating in the program.